CHARACTERIZATION OF THE COMMUNITY PARTICIPATION MODEL IN THE MOSQUE CONSTRUCTION PROCESS (CASE STUDY: CONSTRUCTION OF MOSQUES IN DEMAK REGENCY) - Kusyanto, Mohhamad; Triyadi, Sugeng; Wonorahardjo, Surjamanto (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2019)
This research is based on the phenomenon of community participation in the development of domed mosques in Indonesia. Community participation was identified based on capability and the nature of the community. This paper compares the involvement of people in coastal areas of Demak to the participation of people in Demak city center in Central Java, Indonesia. Data was collected through interviews with the community and stakeholders in the construction of the mosques. The results of the study indicate there are differences in the communities’ capabilities, especially concerning financing and knowledge. Different characteristics also in the total floor area of the mosque building that was built by the community. These differences have an impact on the length of time needed to construct the mosque.